Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/glia.23265
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of TRPM2 channel in Aβ42‐induced microglial activation and generation of tumor necrosis factor‐α

Abstract: Amyloid β (Aβ)-induced neuroinflammation plays an important part in Alzheimer's disease (AD). Emerging evidence supports a role for the transient receptor potential melastatin-related 2 (TRPM2) channel in Aβ-induced neuroinflammation, but how Aβ induces TRPM2 channel activation and this relates to neuroinflammation remained poorly understood. We investigated the mechanisms by which Aβ activates the TRPM2 channel in microglial cells and the relationships to microglial activation and generation of tumor necrosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 48 publications
2
49
0
Order By: Relevance
“…In this study, we have also shed light on the downstream signaling pathways in Piezo1‐dependent stimulation of hDP‐MSC migration as well as ATP‐induced P2 receptor‐dependent stimulation of hDP‐MSC migration reported in our previous study . PYK2 is a well‐recognized signaling mechanism transducing Ca 2+ ‐dependent induction of the MEK/ERK signaling pathway . Our results from hDP‐MSCs from three donors showed that Yoda1‐induced cell migration was prevented by inhibiting PYK2 (Figure A‐D) and MEK/ERK (Figure E‐H).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In this study, we have also shed light on the downstream signaling pathways in Piezo1‐dependent stimulation of hDP‐MSC migration as well as ATP‐induced P2 receptor‐dependent stimulation of hDP‐MSC migration reported in our previous study . PYK2 is a well‐recognized signaling mechanism transducing Ca 2+ ‐dependent induction of the MEK/ERK signaling pathway . Our results from hDP‐MSCs from three donors showed that Yoda1‐induced cell migration was prevented by inhibiting PYK2 (Figure A‐D) and MEK/ERK (Figure E‐H).…”
Section: Discussionsupporting
confidence: 68%
“…It has been proposed that the Piezo1 channel mediates ultrasound‐induced activation of the MEK/ERK signaling pathway in rat DP‐MSCs . The proline‐rich tyrosine kinase 2 (PYK2) is well‐known as a signaling molecule downstream of intracellular Ca 2+ and plays a critical role in mediating Ca 2+ ‐dependent induction of the MEK/ERK pathway in monocyte, microglial, and neuronal cells . There is evidence for involvement of PYK2 in cancer cell migration, but it is unclear whether PYK2 plays a role in the regulation of MSC migration.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we report that alongside its well-characterised function in resolving inflammation and efferocytosis [40], Fpr2/3 activation can reverse oAβ-induced ROS production through deactivation of NADPH oxidase activity. Activation of microglial NADPH oxidase by oAβ is well supported [41,42], and may be critical in triggering neuroinflammation, given the damaging effects of oxidative stress for neurones, as has been reported in traumatic brain injury [43]. Future work will determine whether the in vitro findings we report here can be extended to the in vivo situation, but if so, they suggest that the use of Fpr2/3 agonists capable of reversing NADPH oxidase activation may be of therapeutic potential for AD.…”
Section: Discussionmentioning
confidence: 99%
“…45) More recently, Alawieyah Syed Mortadza et al report that exposure to 10-300 nM Aβ42 induces concentration-dependent microglial activation and generation of TNFα that are ablated by genetically deleting of TRPM2 or pharmacologically inhibiting TRPM2, revealing a critical role of TRPM2 in Aβ42-induced microglial activation. 46) These reports shed light on our understanding of the mechanisms of chronic cerebral hypoperfusion-related inflammation, and suggest a novel therapeutic target for the treatment of cognitive impairment in CNS diseases.…”
Section: Microglial Trpm2 Channels In Cognitive Impairment In Cns Dismentioning
confidence: 96%